Utilization of Smartphone Applications in Improving Basketball Jump Shoot Skills - Irpan Abdurahman; Asep Hadi Hambali; Lutfi Nuryasa (Journal of Physical and Outdoor Education, 2026)
Proper training techniques are essential for developing basketball skills, particularly the Jump Shoot, which requires arm muscle strength and shooting accuracy. This study aimed to analyze the effect of arm muscle strength exercises using the Home Workout No Equipment application on students’ Jump Shoot performance in extracurricular basketball activities. The research employed a quasi-experimental method with a One Group Pretest –Posttest Design conducted over five weeks. The subjects were twelve male students selected through purposive sampling. The research instrument consisted of a Jump Shoot skill test administered before and after the treatment. The results showed an increase in the mean score from 4.83 in the pretest to 7.50 in the posttest. Statistical analysis indicated that the data were normally distributed and homogeneous, with a significant difference between pretest and posttest results. These findings suggest that arm strength training using a smartphone-based application has a positive effect on improving basketball Jump Shoot skills. Therefore, smartphone workout applications without equipment can serve as an effective alternative to enhance basic sports techniques in school settings.